The Extended Lateral Forehead Flap: Today as Was 50-years Ago - Supit, Laureen; Sudjatmiko, Gentur (Jurnal Plastik Rekonstruksi, 2012)
Background: In the era of surgical advances where institutional pride and status resonates with their progress in the minimal invasives, latest technologies, stem cells, and supermicrosurgeries; some things in plastic surgery never change. The extended lateral forehad flap (ELFF) was first introduced by Ian McGregor in 1963 to reconstruct an intraoral defect, he called it the temporal flap. Gillies and Millard each modified and utilized the flap for patching various facial and intraoral defects and published their experience a year later. Until today in 2012, the ELFF is still largely useful for the reconstruction of wide defects post neoplasms ablation in the face or oral region, which would otherwise require distant flaps or free flaps.Patients and Methods: Three cases of oral and perioral carcinoma were resected and reconstructed using the ELFF to cover for: a full-thickness cheek defect including the lip commisure, an inner oral lining, and a hemipalatal defect.Results: In all, the flaps were tunneled subcutaneously, and donor area grafted by full-thickness skin. All flaps survived and functional outcomes are attained in all patients, with acceptable aesthetic results.Summary: A flap once introduced 49 years ago, is today as consistent and applicable in plastic surgery. This article is an appraisal to the ELFF, and a reminder to the general plastic surgeons, of the simple yet versatile role of ELFF in the reconstruction of facial and intraoral defects.